The Problem of Islamic Leadership in the Modern Era and Its Solutions - Mira Anggela; Rosi Mubarokah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
Leadership in Islam is an important aspect grounded in the values of the Qur’an and Hadith, such as trustworthiness, justice, and deliberation. However, in practice, Islamic leadership in the modern and globalized era faces various challenges, including changes in social values, technological developments, and the gap between ideal concepts and reality. This study aims to analyze the concept of leadership in Islam, identify the problems faced in the modern era, and formulate solutions based on Islamic teachings. This research employs a qualitative approach using a library research method. Data were collected from various literature sources such as books, scientific journals, and previous studies, then analyzed using descriptive qualitative techniques. The results of the study indicate that leadership in Islam is not merely structural in nature, but also encompasses moral and spiritual dimensions as a trust (amanah) in safeguarding religion and managing the life of the community. The problems faced include authoritarian tendencies, internal conflicts, weak leadership capacity, as well as the challenges of globalization and digitalization. The proposed solutions are the consistent implementation of leadership based on Islamic values and the development of transformational leadership with a prophetic character by emulating the qualities of the Prophet Muhammad SAW (shiddiq, amanah, tabligh, and fathanah). Thus, the ideal Islamic leadership is leadership that is able to integrate spiritual, moral, and professional values in a balanced manner, so that it remains relevant and capable of facing the challenges of the times, particularly in the context of Islamic education.